Partial Budget Analysis of a Diversified Small Scale Oil Palm Farms in a Changing Climate in Imo and Delta State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
Small scale oil palm farmers and /or households, business owners must often make decisions about changes they are either contemplating making or that have to be made. The partial budget is a useful tool for farm managers when these situations arise. There is dearth of information on whether the small change farmers make will decrease, increase or not change net income. A partial budget helps farm owners/managers evaluate the financial effect of incremental changes. Data were analyzed using Partial budget Analysis. Results showed that Net benefit from diversification (N268, 800) is higher than that from oil palm farmers who adopted monoculture technology (N128, 100). Results show that the Rate of return of switching and/or changing from monoculture to diversification is 1.26. Since the alternative change is more economical and greater than one (1), it was recommended that the change to diversification which can reduce financial risk associated with climate change should be accepted and put into practice by farmers in the study area.
Keywords: Adaptation strategy; Climate change; Diversification; Oil palm monoculture; Partial budget